Study of low temperature plasma activated wafer bonding - Yeo, Thomas Peng Siong. (2013)
A 2-inch GaAs and Si were bonded via Argon (Ar) plasma activation. The effects brought by plasma parameters of exposure time, pressure and radio-frequency (RF) power were investigated through statistical means and characterization tools such as Atomic Force Microscopy (AFM) and Video Contact Angle System (VCA). RF power was found to have the largest influences on the bond energy. The highest specific bond energy is associated with 30 s, 120 mT and 200 W plasma conditions and 140 oC low temperature anneal was 424 mJ/m2. Through the present work, it may serve to integrate a III/V compound material to Si to demonstrate the simplicity in monolithic integration through which processed CMOS Si wafer could be combined with photoelectronics III-V compounds on a standalone platform.